Neurofilament levels are associated with blood-brain barrier integrity, lymphocyte extravasation, and risk factors following the first demyelinating event in multiple sclerosis - Uher, Tomas; McComb, Mason; Galkin, Shery; Srpova, Barbora; Oechtering, Johanna; Barro, Christian; Tyblova, Michaela; Bergsland, Niels; Krasensky, Jan; Dwyer, Michael; Havrdova, Eva Kubala; Posova, Helena; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2021)
BACKGROUND: Increased blood brain barrier (BBB) permeability, CNS inflammation and neuroaxonal damage are pathological hallmarks in early multiple sclerosis (MS). OBJECTIVE: To investigate the associations of neurofilament light chain (NfL) levels with measures of BBB integrity and central nervous system (CNS) inflammation in MS during the first demyelinating event. METHODS: Blood and cerebrospinal fluid (CSF) were obtained from 142 MS (McDonald 2017) treatment-naive patients from the SET study (63% female; age: 29.7 ± 7.9 years) following the disease onset. NfL, albumin, immunoglobulin G (IgG), and immunoglobulin M (IgM) levels were measured in CSF and blood samples. Albumin quotient was computed as a marker of BBB integrity. Immune cell subset counts in CSF were measured using flow cytometry. MS risk factors, such as Human leukocyte antigen DRB1 locus gene (HLA DRB1)*1501, anti-Epstein-Barr virus (EBV) antibodies, and 25-hydroxy vitamin D3, were also measured. RESULTS: Higher serum NfL (sNfL) levels were associated with higher albumin quotient (p < 0.001), CSF CD80+ (p = 0.012), and CD80+ CD19+ (p = 0.015) cell frequency. sNfL levels were also associated with contrast-enhancing and T2 lesions on brain magnetic resonance imaging (MRI; all p ⩽ 0.001). Albumin quotient was not associated with any of the MS risk factors assessed. sNfL levels were associated with anti-EBV viral capsid antigen (VCA) IgG levels (p = 0.0026). CONCLUSION: sNfL levels during the first demyelinating event of MS are associated with greater impairment of BBB integrity, immune cell extravasation, and brain lesion activity on MRI.
Keywords: Young Adult; Blood-Brain Barrier; Male; biologické markery; Risk Factors; Biomarkers; mladý dospělý; Intermediate Filaments; Multiple Sclerosis; biomarker; MRI; intermediární filamenta; Adult; dospělí; mužské pohlaví; lymfocyty; multiple sclerosis; Neurofilament Proteins; lidé; ženské pohlaví; Humans; Lymphocytes; Epstein–Barr virus; rizikové faktory; roztroušená skleróza; Neurofilament light chain; blood–brain barrier; Female; neurofilamentové proteiny; hematoencefalická bariéra